The Impacts of Pieh Marine Protected Area on Reef Fish Resources In Its Adjacent Areas - Reny Puspasari; Budi Nugraha; Puput Fitri Rachmawati; Rita Rachmawati; Dian Oktaviani; Andriyanto Hanif (Bogor Agricultural University, Indonesia, 2023)
Reef fish have a high economic value. Excessive fishing causes degradation of reef fish resources, as has occurred in the West Sumatera waters. Marine protected areas (MPA) offer one of the better management strategies in support of the restoration of the overexploited fish resources by protecting fish habitat and limiting exploitation. This study aims to analyze the impacts of the establishment of MPA on reef fish resources in its adjacent areas. The research was carried out in Pieh MPA and its adjacent areas located in the West Sumatra waters. Fishing experiments were conducted inside the core zone of the MPA and the catch was compared to similar experiments outside MPA. The result showed that the catch per unit effort (CPUE) of reef fishes in the core zone of MPA was 2.47 times higher than that of in the outside of MPA. However, the size composition was not significantly different between those two areas, except for Lutjanus russellii, which shows that the maximum length inside MPA was about 2.5 times higher. The length and weight of Epinephelus areolatus were analyzed to determine the biological condition of the grouper caught in both areas. The length-weight analysis shows that 86.67% of E. areolatus were matured. Nevertheless, the length of maturity in the MPA is smaller, indicating there is the impact of epreviously fishing pressure on E. areolatus. Research results showed that the MPA is double in fish abundance.